Traveling Technologies: And Transformations in Health Care - Annegrete Juul Nielsen (Copenhagen Business School (CBS), 2010)
The `health society' is a mainstream reality Kickbusch (2007) argues: “Health, as we understand it and live it today, is not only an outcome of other social and economic developments but a significant defining factor” (ibid: 144). Indeed, it seems difficult to disagree on the general relevance of health to the constitutive dynamics of contemporary societies and organizations. Plenty of policies, politics and programs preoccupied with the health of the worker, the patient, the children, the old or society at large are being launched. The success of these programs is related to their geographical spread. If a health care program does not leave the desk where it first saw light, its chances of influencing those it would like bear down on is bound to be minimal. For a health care program to have an effect it must be able to travel or move between practices. Some health care programs successfully accomplish this task. They come to be widely adopted, apparently having global relevance, as for example the Chronic Disease Self-Management Program, which has been adopted by countries as diverse as Japan, Australia and Denmark. But how does this happen and which effects does traveling have on a health care program and its place of arrival? This question is the starting point for the following text. In this introduction I start out introducing my approach to health care programs as traveling technologies. Then I very briefly introduce the reader to the two health care programs, Joint Health Plans and the Chronic Disease Self- Management Program, which have served as case studies for the thesis. Finally, I outline the content of the thesis chapter by chapter.
hdl:10398/8212
Keywords: 650